Diagnostic Accuracy of Narrow Band Imaging in Patients with Oral Lichen Planus: A Prospective Study. (14th August 2020) - Deganello, Alberto; Paderno, Alberto; Morello, Riccardo; Fior, Milena; Berretti, Giulia; Del Bon, Francesca; Alparone, Marco; Bardellini, Elena; Majorana, Alessandra; Nicolai, Piero
Abstract : Objective: Oral lichen planus (OLP) is a chronic mucocutaneous immune‐mediated disease affecting 1% to 4% of the worldwide population. Development of malignant lesions is reported but only affects a minority of patients. The aim of our study was to assess the diagnostic potential of narrow band imaging (NBI) in OLP patients; focusing on the identification of high‐grade dysplasia/carcinoma in newly developed lesions. Methods: Prospective evaluation of 56 patients with histopathologic diagnosis of OLP and presenting newly developed lesions not responding to medical treatment. All lesions were assessed by high‐definition (HD) white light (WL) and HD‐NBI endoscopy. All patients underwent biopsy regardless of the appearance at HD‐WL and HD‐NBI. Histology was defined as "positive" in case of high‐grade dysplasia or carcinoma. Results: Five lesions (9%) were diagnosed as high‐grade dysplasia/carcinoma. In this setting, overall diagnostic potential of HD‐NBI was optimal, with a sensitivity of 100% (95% CI, 48–100), specificity of 96% (95% CI, 86–99), negative predictive value of 100% (95% CI, not calculable), positive predictive value of 71% (95% CI, 39–91), and accuracy of 96% (95% CI, 88–100). Conclusions: Despite the diffuse inflammatory pattern derived from OLP, NBI improved the diagnostic accuracy and the capability to detect high‐grade dysplasia/carcinoma. Level of Evidence: 4 Laryngoscope, 131:E1156–E1161, 2021